Implemintasi Program Pendidikan Kesetaraan Paket B di Pusat Kegiatan Belajar Masyarakat (PKBM) Tim Suara Masyarakat Dawuan Kecamatan Cikampek Kabupaten Karawang - Nurul Ijatu Zahro; Sutarjo Sutarjo; Ratna Sari Dewi (Peneliti.net, 2022)
The purpose of this study was to describe the implementation of the Package B Equality Education Program at PKBM (Community Learning Activity Center) Dawuan Community Voice Team, Cikampek District, Karawang Regency along with the supporting and inhibiting factors of program implementation. This study uses an approach with a descriptive method. This research was conducted at the Community Learning Activity Center of the Dawuan Community Voice Team. The subjects of this study consisted of 4 people, namely, 1 manager, 1 educator, and 2 students. Data collection was done by using the method of observation, interview (interview), and documentation. The stages of research carried out are preparation, place and data analysis. The data analysis used includes three stages (1) data reduction (simplification); (2) data display (presented); (3) verification (drawing conclusions). The results of this study indicate that (1) the Implementation Process of the Package B Equivalence Learning Program in the PKBM of the Dawua Community Voice Team, such as background, objectives, curriculum, strategies and methods, facilities and infrastructure, and evaluation. (2) Supporting factors in the implementation in the form of occurring because of the interest of learning residents or the community who want to get an equivalency education diploma. The inhibiting factors for implementation are: (1) people are busy with their work; (2) There is no consistency in public interest; (3) the community has the characteristics of a thinking paradigm and low enthusiasm for learning.